Japanese medical students' awareness of cardiopulmonary resuscitation in the context of the COVID‐19 pandemic. Issue 1 (24th March 2022) - Machino, Hiromi; Irie, Jin; Hiraki, Katsushige; Ukaji, Yukari; Sawaya, Shunnosuke; Nomura, Osamu; Hanada, Hiroyuki
ABSTRACT: Aim: To evaluate Japanese medical students' awareness of newly recommended cardiopulmonary resuscitation (CPR) and airway management procedures in the context of the coronavirus disease (COVID‐19) pandemic. Methods: An online survey was sent in December 2020 to all medical students at Hirosaki University in Japan. The survey included 15 questions and quizzes regarding prior experience of learning the new CPR guidelines in response to COVID‐19, knowledge of conventional CPR, and COVID‐19 context CPR and airway management procedures. Results: Of all medical students at the university, 457 (57.1%) responded to the survey. Among these, 22% reported that they were knowledgeable about CPR procedure in the COVID‐19 pandemic setting. Prior knowledge of CPR in the context of COVID‐19 was a significant positive predictor of quiz score regarding the CPR procedure ( β = 0.60, P < 0.01) and the airway management procedure ( β = 0.34, P = 0.02) in the context of the COVID‐19 pandemic. Conclusions: Medical students with experience learning the new COVID‐19 context CPR guidelines had sufficient knowledge of CPR and advanced airway management procedures in the setting of the COVID‐19 pandemic. Implementation of a formal medical education curriculum based on the newly recommended CPR and advanced life support guidelines is needed to improve medical students' awareness and skills of CPR and airway management in the context of the COVID‐19 pandemic. We aimed to evaluate Japanese medical students' knowledge regarding cardiopulmonary resuscitation procedures updated for use in the setting of the COVID‐19 pandemic through a survey sent to all medical students at Hirosaki University in Japan. Our results indicate that education in these procedures is effective, and that increased opportunities for receiving such education, such as by implementation into the formal curriculum, could have incredible value: